Control of Common Vole (Microtus arvalis) in Alfalfa Crops Using Reduced Content of Anticoagulants - Goran Jokić; Tanja Blažić (Agronomy, 2021)
The common vole, Microtus arvalis, which is prone to cyclic overpopulation, poses a significant threat to sustainable alfalfa production by either chewing shoots periodically or gnawing and damaging roots permanently. In areas with established vole colonies, the density of alfalfa plants was shown to decrease 55.3–63.4%. Simultaneously, the number of alfalfa shoots decreased by 60.9–71.7%. These experiments were conducted in compliance with an EPPO standard method in alfalfa fields at three geographically remote sites. The experiment tested the efficacy of the most widely used acute rodenticide zinc phosphide (2%), and anticoagulants applied at significantly reduced doses of active ingredients, i.e., bromadiolone (25 ppm) and brodifacoum (25 ppm), as well as a combination of these active ingredients at a low concentration (10 + 10 ppm). Three weeks after treatment, zinc phosphide and brodifacoum achieved the highest average efficacy, at 98.5% and 92.05%, respectively, while the average efficacy of the anticoagulant combination and bromadiolone was 87.2% and 75.5%, respectively. The achieved efficacy of baits based on brodifacoum and the combination of brodifacoum and bromadiolone in controlling common voles indicates their possible utilization in the field. Baits with 25 ppm of brodifacoum and the combination of bromadiolone and brodifacoum (10 + 10 ppm) showed satisfactory results and their introduction could significantly improve pest management programs for rodent control. At the same time, the use of anticoagulant rodenticides with reduced contents of active ingredients would significantly reduce their exposure to non-target animals, especially predators and vultures. By further improving the palatability of tested baits for target rodent species, their efficacy and safety of application would be significantly improved.